2022
DOI: 10.3389/fpls.2022.1038079
|View full text |Cite
|
Sign up to set email alerts
|

Revealing seed color variation and their possible association with yield and quality traits in a diversity panel of flax (Linum Usitatissimum L.)

Abstract: Seed color is a vital quality determinant of flax, significant for consumers’ acceptability, and determines the commercial values of seeds. Also, seed color as a phenotypic marker may be a convenient way to select the plants with desired traits. This study assessed a diversity panel representing 144 flax genotypes from diverse geographical origins for the existence of genetic variability for luminosity (L*) and chromaticity (a* and b*) seed color parameters, seed yield, and quality traits over two years. The g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…The usage of machine vision technology has been extensively implemented across diverse domains of agricultural production [11]. Many studies have presented digital image processing for non-destructive rice seed modification, with the majority of rice seed pictures processed utilizing three key aspects: texture [12], color [13], and morphological [14] features [15]. The author has presented an approach that utilizes the Hue Saturation Value (HSV) colour model for the purpose of classifying the germination status of seeds based on the disparities in colour between the seeds and roots.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The usage of machine vision technology has been extensively implemented across diverse domains of agricultural production [11]. Many studies have presented digital image processing for non-destructive rice seed modification, with the majority of rice seed pictures processed utilizing three key aspects: texture [12], color [13], and morphological [14] features [15]. The author has presented an approach that utilizes the Hue Saturation Value (HSV) colour model for the purpose of classifying the germination status of seeds based on the disparities in colour between the seeds and roots.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A vital quality determinant and an essential part of consumer preferences for flax is seed color, which determines seeds’ commercial values. Apart from its direct influence on the acceptability and nutritional quality of flaxseed, the contents of some substances, such as oil, protein, fatty acid profile, and essential breeding traits, depend on seed color [ 19 – 21 ]. It is essential to understand these associations because indirect and sometimes undesirable selection can occur if two traits travel together.…”
Section: Introductionmentioning
confidence: 99%
“…The genes involved in seed color may even be pleiotropic, meaning a single gene affects two or more distinct phenotypic traits. Therefore, seed color has been confirmed as a phenotypic marker to be an effective tool for selecting plants with desirable traits [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies showed that yellow-seed genotypes had lower seed yield, attributed to the lower vigor, lower germination rate, and lack of flavonoids in yellow seeds (Saeidi and Rowland 1999, Zare et al 2021, Abtahi et al 2022. Abtahi et al (2022) argued that red or brown seed colors may serve as effective markers for the indirect selection of oil-and proteinrich genotypes.…”
Section: Introductionmentioning
confidence: 99%
“…Studies showed that yellow-seed genotypes had lower seed yield, attributed to the lower vigor, lower germination rate, and lack of flavonoids in yellow seeds (Saeidi and Rowland 1999, Zare et al 2021, Abtahi et al 2022. Abtahi et al (2022) argued that red or brown seed colors may serve as effective markers for the indirect selection of oil-and proteinrich genotypes. Because of the importance of seed color in the export market, this trait is included in all flax breeding programs (Mittapali and Rowland 2003, Sudarshan et al 2017, Zare et al 2021, Abtahi et al 2022.…”
Section: Introductionmentioning
confidence: 99%